Improving the efficiency of post-digestion method in extracting microplastics from gastrointestinal tract and gills of fish. (December 2020) - Jaafar, Norhazwani; Musa, Syafiq M.; Azfaralariff, Ahmad; Mohamed, Mazlan; Yusoff, Abdul Hafidz; Lazim, Azwan Mat
Abstract: Post-digestion treatment is an important step during sample preparation to facilitate the removal of undigested materials for better detection of ingested microplastics. Sieving, density separation with zinc chloride solution (ZnCl2 ), and oil extraction protocol (OEP) have been introduced in separating microplastics from sediments. The clean-up methods are rarely highlighted in previous studies, especially in the separation of microplastics from marine biota. Thus, this study proposed and compared the suitability of three techniques, which can reduce the number of undigested particles from the digestate of GIT and gills. Our result has shown excellent removal of non-plastics materials and reduces the coloration of filter paper in all treated samples. Both sieving and density separation achieved optimum post-digestion efficiencies of >95% for both GIT and gill samples, which former showed no effect on polymer integrity. Additionally, high recovery rate was obtained for the larger size microplastics (>500 μm) with approximately 97.7% (GIT) and 95.7% (gill), respectively. Exposure to the ZnCl2 solution led to a significant loss of smaller size PET and changed the absorption spectrums of all tested polymers. Particle morphology determined by SEM revealed such exposure eroded the surface of PET fragments and elemental analysis has shown detectable peaks of zinc and chlorine appeared. Low microplastics recoveries were achieved through OPE and residue of oil was observed from the infrared spectrum of all tested polymer. The findings demonstrate sieving with size fractioning can provide exceptional removal of non-plastics materials from the digestate of GIT and gill samples. Graphical abstract: Recommended post digestion protocols for removal of non-plastics materials for digestate of GIT and gill of fish. Image 1 Highlights: Density separation with ZnCl2 solution and oil extraction protocol as post-digestion in biota sample are not advisable. ZnCl2 solution corroded the surface of PET and changes spectra of PP and LDPE. Sieving has effectively reduced interference of non-plastics materials from digestate and coloration on filter.